Development of Proniosome Gel Formulation for CHIKV Infection - Ayça Altay Benetti; Ma Thinzar Thwin; Ahmad Suhaimi; Ryan Sia Tze Liang; Lisa Fong-Poh Ng; Fok-Moon Lum; Camillo Benetti (MDPI AG, 2024)
Given the increasing aging population and the rising prevalence of musculoskeletal diseases due to obesity and injury, urgent research is needed to formulate new treatment alternatives, as current options remain inadequate. Viruses can exacerbate arthritis and worsen symptoms in patients with pre-existing osteoarthritis. Over the past decade, the chikungunya virus (CHIKV) has emerged as a significant public health concern, especially in Asia and South America. Exploring natural products, such as berberine, has shown promise due to its anticatabolic, antioxidative, and anti-inflammatory effects. However, berberine's low stability and bioavailability limit its efficacy. We hypothesized that encapsulating berberine into a proniosome gel, known for its ease of preparation and stability, could enhance its bioavailability and efficacy when applied topically, potentially treating CHIKV infection. Our investigation focused on how varying berberine loads and selected excipients in the proniosome gel influenced its physical properties, stability, and skin permeability. We also examined the biological half-life of berberine in plasma upon topical administration in mice to assess the potential for controlled and sustained drug release. Additionally, we analyzed the antioxidant stress activity and cell viability of HaCaT keratinocytes and developed a lipopolysaccharide-stimulated cell culture model to evaluate anti-inflammatory effects using pro-inflammatory cytokines. Overall, the research aims to transform the treatment landscape for arthritis by leveraging berberine's therapeutic potential.